Content and Audience Commodification Related to the Ferdy Sambo Case in the Perspectives of Media Political Economy:: Review of News Coverage on KompasTV and iNewsTV - Wahzudin, Ervan; Haditama, Haditama; Setianingrum, Vinda Maya (The Journal of Society and Media, 2023)
The murder of Brigadier Yoshua involving former Division of Professionalism and Security of the Indonesian National Police, Ferdy Sambo, along with some people close to him, has attracted public attention for months. The development of the case was also monitored by the mass media, including national television. This study aims to analyze content and audience commodification related to the Ferdy Sambo case by KompasTV and InewsTV media. This study uses a descriptive qualitative methodology, using Vincent Mosco’s political economy theory. The data source used is primary data in the form of in-depth interviews and observations. The results of this study indicated that both KompasTV and iNews TV had commodified content and audience commodification for broadcasting in the case that ensnared Ferdy Sambo with various forms of news programs. Both media did this to get the maximum profit.